2000
DOI: 10.1038/sj.onc.1203740
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal instability and p53 inactivation are required for genesis of glioblastoma but not for colorectal cancer in patients with germline mismatch repair gene mutation

Abstract: We have previously reported high-frequency microsatellite instability (MSI-H) and germ-line mismatch repair gene mutation in patients with unusually young onset of high-grade glioma. Some of these patients developed metachronous MSI-H colorectal cancer and conformed to the diagnosis of Turcot's syndrome. Frameshift mutation of TGFbRII was present in all the colorectal carcinomas but not in brain tumours. We further characterized the genetic pathways of tumour evolution in these metachronous gliomas and colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…A second group of colorectal cancers are near diploid, but show substantial microsatellite instability (MIN), due invariably to de®ciency in mismatch repair Ionov et al, 1993;Thibodeau et al, 1993;Peltomaki et al, 1993;Liu et al, 1996). Such tumours often but not always express normal p53 and display relatively few chromosome imbalances as detected by comparative genomic hybridization (CGH) (Ionov et al, 1993;Remvikos et al, 1995;Schlegel et al, 1995;Cottu et al, 1996;Konishi et al, 1996;Olschwang et al, 1997;Leung et al, 2000). Recently, we have drawn attention to a further group associated with neardiploid DNA content, few examples of chromosome imbalances, and stable microsatellite DNA (Georgiades et al, 1999), here called the microsatellite and chromosome stable (MACS) group.…”
mentioning
confidence: 99%
“…A second group of colorectal cancers are near diploid, but show substantial microsatellite instability (MIN), due invariably to de®ciency in mismatch repair Ionov et al, 1993;Thibodeau et al, 1993;Peltomaki et al, 1993;Liu et al, 1996). Such tumours often but not always express normal p53 and display relatively few chromosome imbalances as detected by comparative genomic hybridization (CGH) (Ionov et al, 1993;Remvikos et al, 1995;Schlegel et al, 1995;Cottu et al, 1996;Konishi et al, 1996;Olschwang et al, 1997;Leung et al, 2000). Recently, we have drawn attention to a further group associated with neardiploid DNA content, few examples of chromosome imbalances, and stable microsatellite DNA (Georgiades et al, 1999), here called the microsatellite and chromosome stable (MACS) group.…”
mentioning
confidence: 99%
“…Although mutations in proto-oncogenes (c-ret) as well as DNA MMR genes have been linked to germline tumours (van Puijenbroek et al, 1997;Leung et al, 2000), alteration of EGFR in germcell tumours has not been reported. This study showed that germline tumour cells not only exhibited lower EGFR expression but also were highly sensitive to DNA-damaging drugs, suggesting that the lack of EGFR expression contributes at least in part to the drug sensitivity of germline cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the inactivation of the alleles of the predisposing gene, additional somatic changes in tumor tissues may make a difference. In TS patients with (heterozygous) germline mutation in MSH2, TP53 inactivation and chromosomal instability were found to be required for the genesis of glioblastoma but not for colorectal carcinoma, which in turn seemed to require TGFβRII frameshift mutation (Leung et al, 2000).…”
Section: Molecular Characteristics Of "Syndromic" Brain Tumorsmentioning
confidence: 99%
“…The loss of MMR protein expression may (Leung et al, 2000) or may not (Gylling et al, 2008) lead to MSI (Table 4). Since the detection of MSI by conventional techniques requires the presence of at least one major tumor clone which exhibits microsatellite repeat length deviating from the normal allele size, the apparent absence of MSI in brain tumors may have an alternative explanation based on clonal heterogeneity.…”
Section: Lynch Syndrome-associated Brain Tumorsmentioning
confidence: 99%